Biodiversity and distribution of rabbitfish (Siganidae) in Tanakeke Island, South Sulawesi, Indonesia - AWALUDDIN AWALUDDIN; BUDIMAWAN BUDIMAWAN; NADIARTI NADIARTI; YAYU ANUGRAH LA NAFIE (Society for Indonesian Biodiversity, 2024)
Abstract. Awaluddin, Budimawan, Nadiarti, Nafie YAL. 2024. Biodiversity and distribution of rabbitfish (Siganidae) in Tanakeke Island, South Sulawesi, Indonesia. Biodiversitas 25: 2756-2762. The purpose of this research is to analyze the biodiversity of rabbitfish (Siganidae) in Tanekeke Island, South Sulawesi, Indonesia including species diversity, richness, evenness, and dominance. Data on Siganidae fish catches were collected from four different stations on Tanakeke Island, where each consisting of inside and outside bay zones. The data collection involved recording the total number of Siganidae fish caught with gillnet in each zone every month for a year. The caught fish were identified and categorized by species. A total 1,7421 were collected, with 1,5181 from inside the bay and 224 from outside the bay. The result indicated that species was dominated by Siganus canaliculatus (Park, 1797) with a frequency of 952 individuals (62.70%) inside the bay and 173 individuals (77.50%) outside the bay. Siganus guttatus (Bloch, 1787) ranks second, with 155 individuals (10.20%) inside the bay and 16 individuals (97.20%) outside the bay, followed by Siganus javus (Linnaeus, 1766), Siganus fuscescens (Houttuyn, 1782), Siganus punctatus (Schneider & Forster, 1801), and Siganus virgatus (Valenciennes, 1835). This research provides important insights that could greatly influence social and cultural aspects of local communities that depend on fisheries resources. The findings suggest that the bay provides more stable conditions that support the growth of rabbitfishes, allowing local communities for manage and conservation their fisheries resources.